Seroepidemiological Study of Human Toxoplasmosis in Females in Ardabil City, 2019-2020 - Roya Houshmandi Khaneghahi; Shahram Habibzadeh; Farhad Pourfarzi; Behnam Mohammadi Ghalehbin (Journal of Ardabil University of Medical Sciences)
Background: Toxoplasmosis is a disease caused by an obligate intracellular protozoan called Toxoplasma gondii. Consumption of raw or undercooked meat infected with tissue cysts and consumption of parasite oocysts are considered the main ways of parasite transmission to humans. The most severe complications of toxoplasmosis occur in people who have an ineffective immune system, as well as during pregnancy. Since the awareness of the prevalence of toxoplasmosis in different population groups and geographical areas and the risk factors involved in it, is one of the most important indicators which can be estimated the risk of infection in any society, this study aims to know the extent of prevalence of anti-toxoplasma antibody in  serum and some risk factors related to it in females in Ardabil city. Methods: Three hundred forty nine female of Ardabil city were randomly selected based on the files available in health centers. This number was divided into ten-year age groups with an age range of 1-69 years. These people were invited and included in the study if they agreed. The designed questionnaire was completed and blood samples were taken. Serum samples were tested using an ELISA kit to detect anti-Toxoplasma IgG antibody. Results: The prevalence rate of anti-toxoplasma IgG antibody in female residents in Ardabil, aged 1 to 69 years was 45%. The prevalence rate was directly related to increasing age. People’s education level had an inverse relationship with the infection rate. Despite the increase in seropositivity, the prevalence rate in people who had contact with cats was not significant. Also, the prevalence rate had a direct and significant relationship with increasing BMI. Conclusion: The seroprevalence of anti-toxoplasmosis antibody in female people in Ardabil is equal to 45% and is high compared to the world estimates. 70-75% of people of marriageable age are seronegative and are at risk of contracting acute toxoplasmosis during pregnancy, which requires appropriate preventive health policies.